2003
DOI: 10.1128/aem.69.6.3359-3367.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Bioluminescent Construct of Escherichia coli O157:H7 for Hazard Assessments of Long-Term Survival in the Environment

Abstract: A chromosomally lux-marked (Tn5 luxCDABE) strain of nontoxigenic Escherichia coli O157:H7 was constructed by transposon mutagenesis and shown to have retained the O157, H7, and intimin phenotypes. The survival characteristics of this strain in the experiments performed (soil at ؊5, ؊100, and ؊1,500 kPa matric potential and artificial groundwater) were indistinguishable from the wild-type strain. Evaluation of potential luminescence was found to be a rapid, cheap, and quantitative measure of viable E. coli O157… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 52 publications
1
72
0
1
Order By: Relevance
“…For instance, two E. coli strains, C278 and C279 (different by enterobacterial repetitive intergenic consensus sequence (ERIC)-PCR-based genomic fingerprinting), survived differently in soil amended with swine manure (Topp et al, 2003). Moreover, basal production of toxin (Stx) by haemolytic uraemic syndrome-associated E. coli was higher than that by bovineassociated E. coli strains (Ritchie et al, 2003). In addition, a reconsideration of the work of Kudva et al (1998) showed that at 23 1C a toxin-negative strain of E. coli O157:H7 grew and survived better than its toxin-positive counterpart, whereas no such differences were found at lower temperatures.…”
Section: Presence and Diversity Of An Indigenous Microfloramentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, two E. coli strains, C278 and C279 (different by enterobacterial repetitive intergenic consensus sequence (ERIC)-PCR-based genomic fingerprinting), survived differently in soil amended with swine manure (Topp et al, 2003). Moreover, basal production of toxin (Stx) by haemolytic uraemic syndrome-associated E. coli was higher than that by bovineassociated E. coli strains (Ritchie et al, 2003). In addition, a reconsideration of the work of Kudva et al (1998) showed that at 23 1C a toxin-negative strain of E. coli O157:H7 grew and survived better than its toxin-positive counterpart, whereas no such differences were found at lower temperatures.…”
Section: Presence and Diversity Of An Indigenous Microfloramentioning
confidence: 99%
“…E. coli O157:H7 is dangerous because of its resistance to low pH (B2.5), which allows passage through the stomach, its low infective dose (as few as 10 cells) and its high pathogenicity (Tilden et al, 1996). Following tissue invasion, it may even cause death (Ritchie et al, 2003). Moreover, the stx genes were found to be transferable to non-pathogenic E. coli strains, allowing these to enhance their virulence (Herold et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In both microcosm experiments, after allowing 30 d for the establishment and stabilization of the microbial community at a comparable level across all of the treatments, an invading bacterial pathogen [i.e., the genetically marked, nonpathogenic E. coli O157:H7 derivative strain Tn5 luxCDAEB (20)] was introduced into the soil microcosms at approximately 10 8 cfu g −1 dry soil. This established a soil moisture content of 75% of WHC.…”
Section: Methodsmentioning
confidence: 99%
“…The fate of the enterohemorrhagic Escherichia coli (EHEC) O157:H7 in soil is of major concern (18)(19)(20). In this context, the microbial communities that established after soil fumigation were shown to determine the fate of the invading species, whereby reduction in microbial diversity due to progressively enhanced fumigation depths resulted in higher pathogen persistence in soil (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation